2005
DOI: 10.1111/j.1365-2982.2004.00609.x
|View full text |Cite
|
Sign up to set email alerts
|

Is gastric electrical stimulation superior to standard pharmacologic therapy in improving GI symptoms, healthcare resources, and long‐term health care benefits?

Abstract: We conclude that GES is more effective in improving long-term GI symptoms and costs, and decreasing use of healthcare resources than intensive medical therapy, in this sample of patients with the symptoms of GP followed for 3 years. Certain patients with GP form a high-risk group in terms of costs, quality of life, morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
95
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(99 citation statements)
references
References 27 publications
3
95
0
Order By: Relevance
“…In two single center studies, electrical stimulation has been reported to improve nutritional status, limit the need for prokinetic and antiemetic medications, and reduce the need for hospitalizations and supplemental nutrition [4,10]. While the published results of Enterra GES are encouraging, the clinical benefits of GES have not been unequivocally demonstrated.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In two single center studies, electrical stimulation has been reported to improve nutritional status, limit the need for prokinetic and antiemetic medications, and reduce the need for hospitalizations and supplemental nutrition [4,10]. While the published results of Enterra GES are encouraging, the clinical benefits of GES have not been unequivocally demonstrated.…”
Section: Discussionmentioning
confidence: 85%
“…There have been other studies reporting on an individual institution's experience with Enterra GES [4][5][6][10][11][12]. In two single center studies, electrical stimulation has been reported to improve nutritional status, limit the need for prokinetic and antiemetic medications, and reduce the need for hospitalizations and supplemental nutrition [4,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[71][72][73][74][75][76][77][78][79][80][81] The most interesting finding in these studies was the dramatic improvement in nausea and vomiting. Depending on study centres, this improvement was noted in 60-75% of patients.…”
Section: Ges With Short Pulsesmentioning
confidence: 81%
“…[1][2][3][4][5][6][7][8][9] In patients with this disorder, GES therapy with the Enterra system has been shown to: (1) reduce vomiting, (2) improve nausea better than placebo, (3) reduce total symptom severity scores from severe to mild-moderate ranges, (4) increase quality of life, (5) increase weight, (6) decrease use of medications, (7) decrease the use of J-tubes, and (8) decrease medical billing costs compared to medical therapy alone. 6,[10][11][12][13][14][15][16] Several novel GES methods to improve gastric motility have been introduced over the last 20 years, such as multichannel GES, dual-pulse GES, and synchronized GES. [17][18][19][20][21][22][23][24][25][26] The term "gastric neuromodulation" has been used as a term to describe the antiemetic effect of GES therapy, as the symptom improvement is believed to be mediated through neurons and neuronal connectivity.…”
Section: Introductionmentioning
confidence: 99%